Preparation of superhydrophobic nanoplate iron oxide surface on a carbon steel for anti-wetting applications - Cao, Xiaofei (2022)
A simple route to fabricate a surface layer comprising Fe3O4 nanoplates on a carbon steel has been successfully demonstrated using etching treatment followed by annealing in oxygen atmosphere. Different sizes of the Fe3O4 (3 1 1) exposed nanoplates can be fabricated by varying the annealing temperature. Density Function Theory (DFT) calculation proved that the energy of Fe3O4 (3 1 1) surface was the lowest among all exposed facets, which make it most stable. The superhydrophobicity has been realized after modification with trimethoxy silane (HFTMS). Molecular dynamic simulation was further carried out to verify the excellent anti-wettability of the modified surface. In addition, the superhydrophobic surface exhibited a low adhesion with water and displays excellent performance in anti-corrosion, anti-icing and self-cleaning.